2020
DOI: 10.2478/sjs-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Racialization Without Racism in Scholarship on Old Age

Abstract: Population aging and international migration have propelled the aging of ethno-cultural minorities to the forefront of social scientific inquiries. Examining how scholarship on old age makes sense of ethnicity and race has become relevant. Based on a scoping review of peer-reviewed articles published between 1998 and 2017 (n = 336), the present article asks whether the notions of racialization and racism inform this scholarship and argues that a racism-sensitive research agenda is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Indeed, ethnic inequalities in socio-economic circumstances are directly related to ethnic inequalities in health ( Nazroo, 2001 ). However, policy and academic debates around ethnic inequalities focus almost entirely on socio-economic factors, and largely ignore the underlying processes of structural, institutional and interpersonal racism (see Nazroo & Bécares, 2021 ; Torres, 2020 ). Findings from this study not only cement the evidence on the harm of racial discrimination on health over time, but also bring to light the central role of racism in reduced socio-economic positions for people from minoritised ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ethnic inequalities in socio-economic circumstances are directly related to ethnic inequalities in health ( Nazroo, 2001 ). However, policy and academic debates around ethnic inequalities focus almost entirely on socio-economic factors, and largely ignore the underlying processes of structural, institutional and interpersonal racism (see Nazroo & Bécares, 2021 ; Torres, 2020 ). Findings from this study not only cement the evidence on the harm of racial discrimination on health over time, but also bring to light the central role of racism in reduced socio-economic positions for people from minoritised ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the evidence shows that socio-economic inequalities make a substantial contribution to ethnic inequalities in health ( Nazroo, 2001 ). However, most academic and policy discourses on ethnic inequalities rarely make explicit that the underlying cause of socio-economic disadvantage is racism and discrimination (see Nazroo & Bécares, 2020 ; Torres, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether undocumented immigrants are indigenous or not and racialized as such may also constrain their healthcare access options because of fear of being identified as undocumented; this may place some undocumented immigrants in circumstances where other coethnic networks leverage their power over them by asking for large amounts of money to drive them to get medicine if individuals cannot obtain a driver's license (Cervantes & Menjívar, 2020; Gómez Cervantes, 2019). Systems of racism and being racialized matter for health outcomes (Torres, 2020), but relatively less of this literature has focused specifically on older‐age immigrants' experiences.…”
Section: General Health Outcomesmentioning
confidence: 99%
“…A recent scoping review found that from 429 studies only 1.7% considered experiences of ethnoracial minorities, immigrants (1.1%), and none considered the intersectionality of multiple systems of inequality in the context of this phenomenon (Serrat et al, 2019). By focusing research on the experience of White Americans and colonial structures of civic participation, the literature has erased the civic contributions of Black, Indigenous, Latinx, and immigrants from the global south that occur outside of these formalized spaces (Torres, 2020).…”
Section: Introductionmentioning
confidence: 99%